逆转录聚合酶链式反应(RT-PCR)检测5种养殖石斑鱼的神经坏死病毒 - 陈信忠; 苏亚玲; 龚艳清; 黄丽莎; 俞秀霞; 苏永全 (2004)
神经坏死病毒(Nervousnecrosisvirus)是导致多种海水鱼类神经性病害的致病原。发病及死亡的石斑鱼除了表现神经异常症状外,无明显的临床病症,体表及内脏组织也未发现明显病变及寄生虫感染。2003年4～8月,应用逆转录聚合酶链式反应(RT-PCR)技术从福建南部人工养殖的5种石斑鱼即紫石斑鱼(Epinepheluslanceolatus)、马拉巴石斑鱼(E.malabaricus)、青石斑鱼(E.awoara)、赤点石斑鱼(E.akaara)和云纹石斑鱼(E.moara)中检出5个神经坏死病毒分离株。检测了76份石斑鱼样品,这些石斑鱼NNV病毒的平均感染率约为90%。对这些病毒的RT-PCR产物421bp核酸进行了测序和序列分析,其相同的序列超过99%。将这些序列与GenBank的石斑鱼(Epinephelusspp.)神经坏死病毒相关基因序列作比较,同源性在97%以上。对神经坏死病毒在石斑鱼体内的分布也进行了分析,在脑和眼组织的检出率最高,部分病鱼的肝、脾和肾组织也能检出病毒。结合流行病学特征,可确认神经坏死病毒为该传染病的主要致病原。RT-PCR方法是检测NNV等病原的一种理想的诊断方法。 Nervous necrosis virus (NNV), also called viral encephalopathy and retinopathy (VER), is a serious disease of some cultured marine fish species. The number of fish species affected by this virus has rapidly increased. It has been observed in barramundi (Lates calcarifer), sea bass (Dicentrarchus labrax), turbot (Scophthulmus maximus), groupers (Epinephelus spp.) and other fishes. This disease is characterised by a variety of neurological abnormalities such as erratic swimming behaviour and vacuolation in central nervous tissues and nuclear layers of retina. Some diagnostic measures such as histopathology, fluorescent antibody test, enzyme-labeled antibody test, enzyme-linked immunosorbent assay, electron microscopy, reverse transcription polymerase chain reaction (RT-PCR) detection, cell culture and in situ hybridization have been described to detect the nervous necrosis virus in the OIE Diagnostic Manual for Aquatic Animals, but no diagnosis and treatment report of NNV were found in China. Grouper is becoming a major fish species of mariculture in China and other Southeast Asian countries, as it had a higher economical value than the other commercial farmed fishes. With the rapidly developing grouper aquaculture, mass mortality associated with viral diseases of the fish has been frequently occurred. Among the infectious diseases, viral diseases often caused significant economic losses to the production, and viral nervous necrosis happened most frequently in these countries. In recent years, some cultured groupers in southern China suffered an epidemical disease that caused heavy mortality. The sick or died fishes did not show any pathological signs other than neurological abnormalities. No significant external or internal lesions or parasites were observed. We used two primers, a reverse primer (5'-CGA-GTC-AAC-ACG-GGT-GAA-GA-3') and a forward primer (5'-CGT-GTC-AGT-CAT-GTG-TCG-CT-3') to amplify a target sequence which had a fragment of about 421 bases in five isolates of the grouper nervous necrosis viruses isolated from the cultured groupers, E. lanceolatus, E. malabaricus, E. awoara, E. akaara and E. moara cultivated in southern Fujian, China, by the reverse transcription polymerase chain reaction method from March to August, 2003. A total of 76 fishes were examined and the average infection rate of these groupers infected by NNV was about 90%. The nucleic acid sequences of the five amplicons had been sequenced. They were 99% identical in each other and showed more than 97% homologue with those of NNV strains from other grouper in GenBank. It was proved that the amplified sequence is the conservative area of NNV in grouper. The infected organs of the grouper by the pathogen had also been detected. It was found that the virus could find in most of the brain and eyes of the fishes, and also detected in kidney, spleen and liver in some sick groupers. These results according with the epidemiologic observation indicate that NNV is the major causative agent of the observed mortality occurred in the cultured groupers. The test of RT-PCR was demonstrated a useful method to detect the pathogen of NNV in diagnosis practice because of its quick, simple and accurate properties. The mode of transmission had been discussed, the influent water, sick or died fish and carriage utensils, vehicles, etc might be the most possible factor in this disease. 福建省科技厅科技项目资助(2002N009)